Analysis of the genetic component of systemic sclerosis in Iranian and Turkish populations through a genome-wide association study - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2019)
Objectives. SSc is an autoimmune disease characterized by alteration of the immune response, vasculopathy and fibrosis. Most genetic studies on SSc have been performed in European-ancestry populations. The aim of this study was to analyse the genetic component of SSc in Middle Eastern patients from Iran and Turkey through a genome-wide association study. Methods. This study analysed data from a total of 834 patients diagnosed with SSc and 1455 healthy controls from Iran and Turkey. DNA was genotyped using high-throughput genotyping platforms. The data generated were imputed using the Michigan Imputation Server, and the Haplotype Reference Consortium as a reference panel. A meta-analysis combining both case-control sets was conducted by the inverse variance method. Results. The highest peak of association belonged to the HLA region in both the Iranian and Turkish populations. Strong and independent associations between the classical alleles HLA-DRB1*11:04 [P = 2.10 x 10(-24), odds ratio (OR) = 3.14] and DPB1*13:01 (P = 5.37 x 10(-14), OR = 5.75) and SSc were observed in the Iranian population. HLA-DRB1*11:04 (P = 4.90 x 10(-11), OR = 2.93) was the only independent signal associated in the Turkish cohort. An omnibus test yielded HLA-DRB1 58 and HLA-DPB1 76 as relevant amino acid positions for this disease. Concerning the meta-analysis, we also identified two associations close to the genome-wide significance level outside the HLA region, corresponding to IRF5-TNPO3 rs17424921-C (P = 1.34 x 10(-7), OR = 1.68) and NFKB1 rs4648133-C (P = 3.11 x 10(-7), OR = 1.47). Conclusion. We identified significant associations in the HLA region and suggestive associations in IRF5-TNPO3 and NFKB1 loci in Iranian and Turkish patients affected by SSc through a genome-wide association study and an extensive HLA analysis.
Keywords: SSc; GWAS; Iranian and Turkish populations; risk loci; FUNCTIONAL POLYMORPHISM; SUSCEPTIBILITY LOCI; KAPPA-B; IDENTIFICATION; REVEALS; DISEASE; REGION; RISK; MHC